Unplanned In-Global Clinic Visits, Emergency Department Encounters and Hospital Readmissions following Urological Prosthetic Surgery: Data for Quality Improvement. Issue 2 (3rd March 2020) - McAbee, Kara E.; Pearlman, Amy M.; Deebel, Nicholas A.; Rasper, Alison M.; Terlecki, Ryan P.
Abstract: Introduction: Unplanned and potentially avoidable clinic encounters, emergency department visits and readmissions burden the health care system. We identified and characterized unplanned health care utilization during the 90-day global period following urological prosthetic surgery. Methods: Records of patients undergoing penile prosthesis implantation and/or artificial urinary sphincter placement by a single surgeon between January 2011 and November 2016 were retrospectively reviewed. Unplanned visits to the urology clinic, emergency department and/or hospital for each patient within 90 days of surgery were identified and characterized. Results: Of the 288 surgeries performed during the designated study period 214 were for inflatable penile prosthesis, 59 for artificial urinary sphincter and 15 for a combination. There were 58 unplanned in-global clinic encounters, 13 emergency department visits and 7 hospital readmissions. Unplanned clinic visits were most common for additional teaching, voiding issues and incision concerns, presenting an average of 39 days postoperatively. Emergency department visits were most commonly due to voiding issues and incision concerns, presenting an average of 25 days postoperatively. Hospital readmissions were most common for complications and incision concerns, presenting an average of 23 days postoperatively. Conclusions: Most unplanned visits during the 90-day global period following urological prosthetic surgery do not require hospital readmission. Improved preoperative counseling, instruction before hospital discharge and/or scheduled phone contact with patients during recovery may reduce unnecessary resource use.